2017
DOI: 10.1016/j.bbcan.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mercapturic acid pathway and vicenin-2 for prevention of prostate cancer

Abstract: Prostate cancer (CaP) is often androgen-sensitive malignancy and regresses upon inhibition of androgen signaling. However, CaP, nearly always develops androgen resistance and progresses to aggressive and lethal androgen-independent CaP, which lacks satisfactory therapy. For metastatic CaP, patients are often treated with Taxotere (docetaxel), a cytoskeleton-targeted chemotherapy drug, that provides transient palliative benefit but to which patients rapidly develop drug-resistance. Combination chemotherapy may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Due to Chinese medicine theory claims that it clears heat and nourishes the lungs, Dendrobium officinale is widely used in China to treat lung cancer as an adjunctive therapy in order to improve the life quality of patients. ViceninII, a C-glycoside flavonoid extracted from Dendrobium officinale, has been identified and isolated from various medicinal herbs and has shown multiple pharmacological activities, particularly anti-cancer activities [51,52,53], but none of the previous research has focused on the anti-metastasis effects. Therefore, we wondered whether ViceninII could inhibit the TGF-β1-mediated EMT metastasis of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to Chinese medicine theory claims that it clears heat and nourishes the lungs, Dendrobium officinale is widely used in China to treat lung cancer as an adjunctive therapy in order to improve the life quality of patients. ViceninII, a C-glycoside flavonoid extracted from Dendrobium officinale, has been identified and isolated from various medicinal herbs and has shown multiple pharmacological activities, particularly anti-cancer activities [51,52,53], but none of the previous research has focused on the anti-metastasis effects. Therefore, we wondered whether ViceninII could inhibit the TGF-β1-mediated EMT metastasis of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…ViceninII, or 6,8-di-C-glucoside of apigenin, a nontoxic flavonoid that was originally identified from Vitex lucens wood and that is present in many plant sources in Southern Asia, such as Dendrobium officinale , Urtica circularis , Lychnophora and other species [40,41,42], is an effective anti-inflammatory [43,44,45,46], antiglycation [47], anti-spasmodic [48], antiseptic [49], antithrombotic, and antiplatelet agent [50]. ViceninII exhibits significant anticancer activities that inhibit the growth of prostate cancer (PC-3, DU-145 and LNCaP cells) in-vitro and in-vivo [51,52] and induce apoptosis in hT-29 human colon cancer cells [53]. In addition, many critical literatures has been reported that ViceninII has shown anti-inflammatory effect through the inhibition of TGF-β-induced protein signaling pathway as well as induced apoptosis of lung cancer H23 cell via PI3K/Akt/mTOR signaling [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Vicenin-2 is a nontoxic flavonoid from the herb Ocimum sanctum Linn and Moringa oleifera , which are widely available in the region of Southern Asia. 12 Vicenin-2 has been reported to possess many pharmacological properties that include antioxidant, hepatoprotective, antiinflammatory, and anticancer effects. 13 Vicenin-2 inhibits angiogenesis and decreases the expression of vascular endothelial growth factor in prostate cancer, and it was proven to be effectively absorbed after oral administration in preclinical models, which was correlated with tumor regression.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Vicenin-2 inhibits angiogenesis and decreases the expression of vascular endothelial growth factor in prostate cancer, and it was proven to be effectively absorbed after oral administration in preclinical models, which was correlated with tumor regression. 12 …”
Section: Introductionmentioning
confidence: 99%
“…For example, vicenin-2 is a flavone C -glycoside found in diverse plants including Orchidaceae ( Figure 1 a) [ 7 , 8 , 9 ] and has shown various biological activities, including anticancer [ 10 ], anti-inflammatory [ 11 ], and antioxidant effects [ 12 ]. As a result, recent studies on vicenin-2 have focused on various aspects from the quality control of herbal medicine [ 13 ] to organic synthesis [ 14 , 15 ] to the treatment [ 10 ] or prevention [ 16 ] of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%